BUSINESS ANALYSIS OF CANVAS AND SWOT MODELS (CASE STUDY FOR CULINARY CROSSBREED CAKE "TN. XYZ") - Victor, Victor (Dinasti International Journal of Economics, Finance & Accounting, 2020)
Basket cakes (some call them baskets), named after their printed basket-shaped containers, are cakes made from sticky rice flour and sugar and have a sticky and sticky texture. This cake is one of the typical cakes or mandatory Chinese New Year celebrations. "TN.XYZ" Basket Cake Business is a domestic company that makes basket cakes that are normally made and marketed each year before the Chinese New Year celebrations. The value proposition of “TN.XYZ” Basket Cake is a typical Peranakan cuisine that is marketed before the Chinese New Year. The channel chosen by the owner to verbally sell his products using traditional methods also uses digital technology via social media Instagram. In addition, the owner performs consignment storage in traditional markets and sells products to retail outlets as product demand increases. Customer relationship from Kue Basket "TN.XYZ" via social media Instagram. WhatsApp is also used to upload the results of testimonials from consumers who have already purchased "TN.XYZ" cake basket products through online media.